O microempreendedor individual e a pandemia: um estudo sobre os microempreendedores que atuam no setor de venda de alimentos em Santarém-Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Entrepreneurship is currently presented as a field of knowledge in transformation, because with the current health crisis of covid-19, some people were fired from their jobs and saw the opening of their own business as an alternative to support their family. But, this is not a rule, several active microentrepreneurs, had their venture before the pandemic and with the impact of it had to articulate so they didn't have to close the doors. Addressing the issue of MEIs that work with the sale of food, the present work aimed to present the profile of a portion of microentrepreneurs in the municipality of Santarém-PA. Therefore, a bibliographic research was carried out, which made it possible to know a little more about the issue of the Individual Microentrepreneur (MEI), as well as its characteristics and main benefits for those who want to formalize their own business. There was the application of semi-structured questionnaires that addressed qualitative and quantitative issues. In total, there were twelve interviewees who work in the sale of food, in kiosks and stalls, distributed in six points of the municipality, which provided important data for the purposes of the study. From the point of view of the interviewees, the pandemic was totally negative, as most had to close their doors in a period of time and had to work from home, but the issue of clientele decreased dramatically and so did the inflow of money. Considering the reasons for carrying out the present study, in highlighting the small businesses that work in the food sales sector, it is important to note that currently there is a shortage of publication and research in the region on the topic addressed, with this work intends to serve for future studies. academic research.
Keywords: Empreendedorismo; Microempreendedor Individual; Setor de venda de alimentos; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS